Comparison of PERT/CPM and CCPM Methods in Project Time Management - Takami Narita, Taynara; Alberconi, Caio Henrique; Souza, Fernando Bernardi de; Ikeziri, Lucas (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose: Evaluate and compare PERT/CPM and Critical Chain Project Management (CCPM) techniques, from the Theory of Constraints (TOC), in relation to indicators of delivery time estimation and reliability in meeting established deadlines. Theoretical framework: The research is based on the time management theory established by the PERT/CPM and CCPM methods. Design/methodology/approach: This work has an experimental character, using a method of computer simulation by applying the Promodel software. A fictitious project environment managed by PERT/CPM and CCPM techniques was modeled in order to evaluate and compare their performances in terms of estimation of, and compliance with, project completion deadlines. Findings: The results obtained showed that the CCPM method proved to be more effective in reducing project completion time and meeting established deadlines. Conversely, the PERT/CPM method increased planned project completion time by 189%. Research, Practical & Social implications: Many managers assume that the best approach to project planning, especially when aiming for short and reliable deadlines, is to allocate margins of safety to each scheduled activity. This research reinforced the already widely held perception of TOC that, due to certain ordinary human behaviors, local optimizations do not guarantee, and usually adversely effect, good global results. Originality/value: There is a lack of research comparing PERT/CPM and CCPM techniques through modeling and computer simulations of project environments subjected to certain degrees of uncertainty, particularly in terms of performance variables such as those studied here. The results of this research, therefore, address this opportunity, bringing to light comparative scenarios and explanations for the different behaviors observed. Keywords: Computational Simulation; Project Management; Goldratt; Critical Chain; CCPM; PERT/CPM.